Global surgery and climate change: how global surgery can prioritise both the health of the planet and its people - Sophia Chen; Yvan Zolo; Lumbani Ngulube; Moses Isiagi; Salome Maswime (BMC Surgery)
Abstract Climate change is an emerging global health crisis, disproportionately affecting low- and middle-income countries (LMICs) where health outcomes are increasingly compromised by environmental stressors such as pollution, natural disasters, and human migration. With a focus on promoting health equity, Global Surgery advocates for expanding access to surgical care and enhancing health outcomes, particularly in resource-limited and disaster-affected areas like LMICs. The healthcare industry—and more specifically, surgical care—significantly contributes to the global carbon footprint, primarily through resource-intensive settings, i.e. operating rooms that generate greenhouse gases and substantial medical waste. Therefore, Global Surgery efforts aimed at improving surgical access through an increase in surgical volumes may inadvertently exacerbate health challenges for vulnerable populations by further contributing to environmental degradation. This predicament is particularly pronounced in LMICs, who already suffer from a disproportionate share of the global burden of disease, and where the demand for surgery is rising without corresponding resilient infrastructure. LMICs face a double jeopardy of health inequity coupled with climate vulnerability. As a movement positioned to improve health around the world, Global Surgery has an increasingly significant role in envisioning and ensuring a sustainable future. Global Surgery initiatives must prioritise sustainable infrastructure in both high-income countries (HICs) and LMICs, all while accounting for the unequal polluting contributions between HICs and LMICs and, consequently, moral responsibilities moving forward. Moreover, through targeting upstream causes of poor health at urban and perioperative levels, Global Surgery’s interventions may help to reduce the global burden of disease—avoiding preventable surgeries and their carbon footprints from the outset. Altogether, Global Surgery and climate change are two matters of social justice whose solutions must synergistically centralise the health of both the planet and its most vulnerable people.